KOH activated carbons from Brazil nut shell: preparation, characterization, and their application in phenol adsorption (2022)
Activated carbons named AC105 and AC11 were prepared from Brazil nut shells using the weight ratios of Brazil nut shells: KOH of 1:0.5 and 1:1, respectively. The prepared materials were characterized using different techniques and applied to remove phenol from the aqueous solution through adsorption. The characterization data showed that both materials presented similar properties, with AC11 exhibiting a slightly higher specific surface area (332.2 m2 g–1) than AC105 (314.3 m2 g–1). The kinetic study showed that AC11 reached the process equilibrium faster than AC105, and the Elovich model was best suited to the kinetic data for both adsorbents. The equilibrium data followed the Sips model; the maximum adsorption capacities were 55.16 and 68.52 mg g–1 for AC105 and AC11, respectively. The application of the materials in the treatment of a simulated industrial effluent showed removal efficiencies of 28.05% and 48.20% for AC105 and AC11, respectively. Therefore, through the adsorption results, AC11 proved to be more efficient towards phenol removal and is a promising alternative for treating wastewater containing this contaminant.